Results of the complex evaluation of bryndza cheese and the byproduct milk whey with the use of enzyme MTG and its activity degree during storage - K. A. Kanina; N. A. Zhizhin; E. A. Karakulova; P. R. Atanasov (Пищевые системы)
The paper examines the question of using the enzyme microbial transglutaminase (mTG) for bryndza cheese production. Microbial transglutaminase belongs to the enzyme family that catalyzes formation of bonds between amino groups. One of the problems in production of high-protein products, in particular, cheeses from goat milk is flabbiness of the clot. The use of mTG in the technological process would allow strengthening the product protein matrix, thereby improving its commercial characteristics. When performing the histological investigation of cheeses with this enzyme type to characterize the state of the protein matrix, the authors established that the product protein structure was more condensed compared to the control samples (without mTG), which affected cheese consistency. Consistency became more rubbery negatively influencing the product sensory properties, which are important traits for a consumer when buying a product. Using a Brookfield texture analyzer, it was shown that structural-mechanical characteristics were improved by 1.5 times for cheese samples produced from cow milk and by 2 times for goat cheese when mTG was used. Analysis of the enzyme catalytic activity showed that this enzyme retained its activity throughout the whole storage period, which is a potential hazard for human health. After shelf-life expiration, a change in the mTG activity was not more than 5% relative to the initial levels. The enzyme activity retained not only in cheese but also in the by-product — cheese whey, which made its processing more difficult.